2014
DOI: 10.4161/15384101.2014.958393
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondria-targeted antioxidant SkQ1 restoresαB-crystallin expression and protects against AMD-like retinopathy in OXYS rats

Abstract: Abbreviations: AMD, age-related macular degeneration; RPE, retinal pigment epithelium; SkQ1, 10-(6 0 plastoquinonyl)decyltriphenylphosphonium.Age-related macular degeneration (AMD), a neurodegenerative and vascular retinal disease, is the leading cause of blindness in the developed world. Accumulating evidence suggests that alterations in the expression of a small heat shock protein (aB-crystallin) are involved in the pathogeneses of AMD. Here we demonstrate that senescenceaccelerated OXYS rats-an animal model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…As described earlier, absence of αB crystallin leads to significant attenuation of angiogenesis via modulation of VEGF in models of intraocular diseases [4]. In a recent study, Muraleva et al [90] demonstrated that senescence-accelerated OXYS rat model of dry AMD develop spontaneous retinopathy because of decreased expression of αB crystallin. These above findings support the conclusion that α-crystallins may be effective targets for disease therapy.…”
Section: α-Crystallin and Its Constitutive Peptides As Therapeutic Momentioning
confidence: 93%
“…As described earlier, absence of αB crystallin leads to significant attenuation of angiogenesis via modulation of VEGF in models of intraocular diseases [4]. In a recent study, Muraleva et al [90] demonstrated that senescence-accelerated OXYS rat model of dry AMD develop spontaneous retinopathy because of decreased expression of αB crystallin. These above findings support the conclusion that α-crystallins may be effective targets for disease therapy.…”
Section: α-Crystallin and Its Constitutive Peptides As Therapeutic Momentioning
confidence: 93%
“…There is evidence that a suitable experimental model of AMD is senescence-accelerated OXYS rats, which spontaneously develop a phenotype similar to human age-related disorders including AMD-like retinopathy [5][6][7][8][9][10][11]. Retinopathy that develops in OXYS rats already at a young age corresponds (in terms of clinical manifestations and morphological characteristics) to the dry atrophic form of AMD in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Just as the dry form of human AMD, the initial alterations in the RPE cells later lead to atrophy of the choriocapillaris and the complete loss of photoreceptor cells in the OXYS rats' retinas by the age of 24 months. 12,14,15 Previously, by means of RNA sequencing (RNA-Seq), we determined that the retinopathy in OXYS rats at the first stage (age 3 months) and second stage (age 18 months) develops simultaneously with changes in mRNA levels of hundreds of genes. Most of them are linked to immune responses, inflammation, the response to oxidative stress, Ca 2C homeostasis, and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16] OXYS rats develop retinopathy similar to the dry form of human AMD according to the clinical signs, morphological features, and some molecular changes. In these rats, the clinical signs of retinopathy appear by the age of 3 months during a reduction in the transverse area of the RPE and impairment of choroidal microcirculation.…”
Section: Introductionmentioning
confidence: 99%